Indikator Keterampilan Berpikir Kreatif dalam Lembar Kerja Siswa Laju Reaksi berbasis PjBL - Aisyah Tiara Kusumaningtyas; Omay Sumarna; Sjaeful Anwar (Postgraduate, University of Mataram, 2023)
This study aims to dig up informations about the suitability of creative thinking skill indicators in PjBL student worksheets on reaction rate material in the context of making liquid organic fertilizer from banana peels. The method used in this study is design research at the preliminary research stage and the development or prototyping stage. The preliminary research consisted of analysis of the literature review about project-based learning, creative thinking skills, and liquid organic fertilizer from banana peels. The development of prototyping stage consisted designing project-based student worksheets that designs to develop creative thinking skills and validation process or expert judgement by the validator about the designed worksheets. The results showed that there was a very good suitability (100%) bertween project-based stages and creative thinking skill indicators. There are three indicators of creative thinking skills that can be found in this worksheets, which is fluency thinking, flexibility thinking, and elaboration thinking. This shows that creative thinking skill indicators can be well formulated into project-based student worksheets on reaction rate material